Artificially Positive Crossmatches Not Leading to the Refusal of Kidney Donations due to the Usage of Adequate Diagnostic Tools. (28th March 2013) - Schlaf, G.; Pollok-Kopp, B.; Schabel, E.; Altermann, W.
Abstract : Allografting patients with human leukocyte antigens (HLA) which are recognized by preformed antibodies constitutes the main cause for hyper-acute or acute rejections. In order to select recipients without these donor-specific antibodies, the complement-dependent cytotoxicity crossmatch (CDC-CM) assay was developed as a standard procedure about forty years ago. The negative outcome of pretransplant crossmatching represents the most important requirement for a successful kidney graft survival. The artificially positive outcomes of CDC-based crossmatches due to the underlying disease Systemic Lupus Erythematosus (SLE), however, may lead to the unjustified refusal of adequate kidney grafts. Two prospective female recipients destined for a living as well as for a cadaver kidney donation, respectively, exhibited positive CDC-based crossmatch outcomes although for both patients no historical immunizing events were known. Furthermore, solid phase-based screening or antibody differentiation analyses never led to positive results. Immediate reruns of the CDC-based crossmatch assays using the alternative antibody monitoring system (AMS-)crossmatch ELISA resulted in unequivocally negative outcomes. Consequently both transplantations were performed without any immunological complications for the hitherto follow-up time of 25 and 28 months, respectively. We here show two case reports demonstrating an alternative methodical approach to circumvent CDC-based artefacts and point to the urgent need to substitute the CDC-based crossmatch procedure at least for special groups of patients.